The Influence of Service Quality and Price on Customer Satisfaction: Case Study of PT. Lion Mentari Airlines - Sudarmawan Samidi (International Journal of Business Studies, 2021)
The purpose of this research is to examine the influence of service quality and price partially or simultaneously to customer satisfaction level on using services from PT. Lion Air flight operation at Soekarno Hatta Airport. Quantitative research method is used in this study through questionnaires to 160 respondents. Purposive sampling method was chosen to collect the data, then the data were then analysed using SPSS to achieve the study’s objective. The results showed that service quality and price have significant effect on customer satisfaction simultaneously and partially. This study give contribution for the practitioners in aviation industry to put service quality and price as one of their strategy to increase customer satisfaction, and this study also can be used by academicians and future researchers to enhance their knowledge in the field of marketing and strategic management.